Optimizing The Role Of Regional-Owned Enterprises: Corporate Governance As The Foundation For Regional Fiscal Independence - Rizky Ghozali, Mohammad Irsyaad (CV. Publikasi Indonesia, 2025)
Regionally-Owned Enterprises (BUMD) are positioned as strategic instruments to realize regional fiscal independence, but their performance in aggregate shows the gap between potential and reality. This study aims to analyze the root causes of suboptimal BUMD performance, focusing on governance failures as the main obstacle. Using a qualitative research method with a desk research approach, this study synthesizes data from institutional reports, scientific journals, and case studies. The results of the study show that the performance of BUMDs is structurally hampered by two fundamental problems: the paradox of dual mission between public service obligations and profitability targets, and acute accountability deficits. This deficit is manifested through systemic political interventions in leadership determination, patronage, and widespread conflicts of interest, leading to chronic inefficiencies and financial losses. It was concluded that the transformation of BUMD requires comprehensive governance reforms, including depoliticization of management, strengthening the regulatory framework through special laws, and professionalization of human resources to break the cycle of dependence on the Regional Revenue and Expenditure Budget (APBD).